Beneish model, corporate governance and financial statements manipulation - Ibadin, Peter Okoeguale; Ehigie, Aimienrovbiye Humphrey (Penerbit Universiti Kebangsaan Malaysia, 2019)
This paper examined corporate governance and financial statements manipulation in Nigeria, using the Beneish model. To this end, the Beneish Model was employed to predict the likelihood of financial statements manipulation among the companies in Nigeria while the role of corporate governance variables to this manipulation was examined, using logistic regression analysis. In specific terms, the corporate governance variables of Board Composition, Board Gender Composition, Audit Committee Composition, and Board Dominance were examined as determinants. The data used were extracted from sixty-five (65) quoted companies in the Nigeria Stock Exchange for a 6-year period of 2009-2014. This period a near-crash in the Nigerian stock market with the consequential low ebb in economic activities in Nigeria. Preliminary analysis reveals that most of the companies quoted in the Nigeria Stock Exchange and sampled for this study, based on the Beneish Model, have the probability of manipulating their annual financial statements. Furthermore, results revealed that an increase in the Board Composition defined in the proportion of the Non-Executive Director (NED) on the Board, will increase the likelihood of detecting, preventing and investigating financial statements manipulation in the quoted companies in Nigeria. In addition, it was discovered that, in the Board Gender Composition, an increase in the proportion of female gender in the entire board will increase the likelihood of detecting, preventing and investigating financial statements manipulation. Meanwhile, it was revealed that an increase in the effectiveness and efficiency of the composition of the audit committee may reduce the likelihood of financial statements manipulation in Nigeria companies. Lastly, it was discovered that a decrease in Board Dominance will increase the likelihood of detecting, preventing and investigating misstatements in the annual financial statements of Nigeria companies. It is recommended. in the meantime, to use the Beneish model as a norm to assess the possibility of financial statements manipulation. More stringent measures, such as whistleblowing, ethics, value system, zero tolerance to fraud, just to mention a few, are to be effectively enforced by external regulatory authorities (such as Central Bank of Nigeria, Securities and Exchange Commission and the Nigerian Stock Exchange) to control the activities of the company’s board of directors, as well as the application of Beneish model, would aid the detection of financial statements manipulation.